In vitro anthelmintic activity of three medicinal plants. - *, Adeola; Adewole, I.B,; L.K, Olofintoye, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
In vitro anthelmintic assay of three medicinal plants was conducted to investigate whichplants were anthelmintic. In vitro anthelmintic activity of all the three medicinal plants werecarried out using earthworm at 50, 100, 200mg/ml of plant extracts from Vernoniaamygdalina, Ocimum grattisimum and Talinum triangulare. Results showed that 200mg/mlwas effective concentration for all the medicinal plants. Vernonia amygdalina showed fasteranthelmintic than Ocimum grattisimum and Talinum triangulare.The plants can be used /employed in pharmaceutical industry to be used as anthelminticdrugs for treating livestocks affected with helminths.